التأويل الفاسد ودوره في التكفير عند الجماعات المتطرفة: داعش مثالاً - المنصوري، عبدالواحد زيارة اسكندر; عبدالرضا، حازم عبداللطيف (جامعة البصرة - كلية التربية للعلوم الإنسانية, 2018)
The research tried to shed light on the phenomenon of the Al - Takfer (denying the existence of God) which fascinated the human societies, with monitoring the main sources of the Al - Takfer, which were resulting by the corruption of the religious text interpretation and its understanding according to the desires, with a statement and review of a group of religious texts which were adopted by the extremist groups (ISIS) in the atheism of the Islamic groups through the reading based on the corrupt interpretation that is not based on a particular valid approach, according to the study of the linguistic interpretation.
يحاول البحث تسليط الضوء على ظاهرة التكفير التي أحدثت الفتنة بالمجتمعات الإنسانية، مع رصد المنابع الأساسية للتكفير الديني الناتجة من فساد تأويل النص الديني وفهمه حسب الأهواء والرغبات، مع استعراض مجموعة من النصوص الدينية التي اعتمدتها الجماعات المتطرفة (داعش) في تكفير الفرق الإسلامية من خلال القراءة التي بنيت على التأويل الفاسد الذي لا يستند إلى منهج معين مستدل على صحته، وفق دراسة لغوية تأويلية.
Keywords: التطرف الفكري -- التكفير -- الجماعات المتطرفة -- تنظيم داعش